1996
DOI: 10.1080/095530096145779
|View full text |Cite
|
Sign up to set email alerts
|

Repair of dGMP hydroxyl radical adducts by verbascoside via electron transfer: a pulse radiolysis study

Abstract: The repair activity of verbascoside (VER), isolated from Pedicularis spicata, towards the oxidizing hydroxyl radical adduct of dGMP and its reaction mechanism were studied using pulse radiolysis. Upon pulse radiolysis of nitrous oxide saturated aqueous solution of 2'-deoxyguanosine-5'-monophosphate (dGMP) and VER, it was found that the transient absorption spectrum of the hydroxyl adduct of dGMP decays with the formation of that of the phenoxyl radical of VER, several tens of microseconds after the electron pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…[28"291 Pulse radiolysis studies have provided both spectral [3°-32] and redox [33'34] information on DNA base radicals formed upon one-electron oxidation. Fast chemical repair by antioxidants of the guanyl radical formed upon the reaction of the "OH radicals with guanosine and dGMP [3°' [35][36][37][38] has been demonstrated. Most attention has been paid to the repair of the guanyl radical as guanine is the most easily oxidised of the DNA bases.…”
Section: Introductionmentioning
confidence: 99%
“…[28"291 Pulse radiolysis studies have provided both spectral [3°-32] and redox [33'34] information on DNA base radicals formed upon one-electron oxidation. Fast chemical repair by antioxidants of the guanyl radical formed upon the reaction of the "OH radicals with guanosine and dGMP [3°' [35][36][37][38] has been demonstrated. Most attention has been paid to the repair of the guanyl radical as guanine is the most easily oxidised of the DNA bases.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that the repair mechanism of damaged DNA by PPG molecules is believed through an electron transfer process by the formation of drug-receptor complex in minor groove of the double helix [23,24,45]. The exocyclic nitrogen atom (N2) of guanine in DNA double helix and one of phenolic groups of PPG are involved in electron transfer process.…”
Section: Conformational Searching Of Drug Moleculesmentioning
confidence: 99%
“…2 (inset), follows first order kinetics. The rate constant can be deduced from the slopes by varying the initial concentrations of PPGs (0.02 -0.1 mM) [21,23,24]. The rate constants for studied PPGs and their analogs are gathered in Table I.…”
Section: Experimental Observationsmentioning
confidence: 99%
“…Based on experimental results, the repair mechanism of PPGs has been analyzed and reported [21,23]. It is believed that the repair reaction is achieved via an electron transfer process.…”
mentioning
confidence: 99%
See 1 more Smart Citation